Ayurvedic Management of Shushkakshipaka w. s. r. to Dry Eye Syndrome- A Review. - Shekhawat, Mahipal Singh; Sharma, Aparna (International Research Journal of Ayurveda & Yoga, 2023)
The windows to the soul are the eyes. Since the Vedic and Samhita times, Ayurvedic ancient writings have discussed the eye and its disorders, demonstrating the significance of the eye and ways to protect it. Because of this, eye care has always been a top priority. Clinical characteristics of Dry eye are frequently observed in Suskaksipaka in Ayurveda. It’s common to equate dry eyes to shushkakshipaka. However, a closer examination of the dry eye symptoms reveals two Ayurvedic terms that are closely related to the illness. The first stage of vartma roga (disease of the lid), which is defined as vata prakopa over the surface structures of the eye due to a lack of snigdha bhava, either in the form of abnormal aqueous or lipid component of tear film, which in turn creates difficulty in opening the lids, pricking pain, and a gritty feeling, is known as Krichronmeela. Shushkakshipaka, a sarvakshi disease, appears when pita becomes engaged in the pathophysiology and samprapti deepens into the dhatus over the surface structures of the eye, such as the conjunctiva and cornea.